Solidaritas Sosial Petani Jagung di Desa Papualangi, Kecamatan Tolinggula, Kabupaten Gorontalo Utara - Matuwala, Misna; Hatu, Rauf A.; Bumulo, Sahrain (Dynamics of Rural Society Journal, 2024)
This study aims to examine the social solidarity among corn farmers in Papualangi Village, Tolinggula District, North Gorontalo Regency. A qualitative approach with descriptive analysis was employed. Five corn farmers from Papualangi Village served as informants for this research. Data were collected through documentation, interviews, and observation. The findings indicate the following: First, the Papualangi Village government's role in enhancing the welfare of corn farmers has not been effectively implemented. Second, while corn farmers’ response to social solidarity remains strong, there has been a shift from a previously unpaid system of solidarity to one that employs a wage system. Third, materialism acts as a hindrance; specifically, the wage system provided to workers during corn planting is a form of materialism that inhibits solidarity. Fourth, the wage system's impact on corn farmers includes both positive and negative effects. On the positive side, field observations reveal that the wage system enhances efficiency and accelerates work completion. Additionally, it increases income for workers who benefit from earning extra money. Besides the direct economic benefits, the wage system can positively influence social solidarity within the farming community. However, the shift to a wage system may also have adverse effects. One potential negative consequence is a decline in social solidarity among farmers. Some may prefer paying workers rather than relying on traditional mutual cooperation, which can diminish the sense of dependency and communal involvement.